The Wrong Acquired Experiences and Their Effect On Learning Correct Movements In Freestyle swimming - Salahaddin, Mustafa (Journal of Physical Education, 2008)
The Aim of the research is to identify the effect of past wrong experiences on learning correct movements. It also aims at identifying the differences between students with wrong experiences and those who don’t have any experience in swimming while acquiring freestyle swimming . The research hypothesized that wrong past experiences have an effect on acquiring new correct movements in freestyle . He also hypothesized that there are significant statistical difference in the tests used for both experimental groups. The researcher used the experimental method. The subjects consisted of (22) students of the college of physical education divided into two equal experimental groups. The researcher used two tests to measure the level of learning the correct movements of freestyle by the subjects. The first test included the teache’s evaluation of the movements through 15m freestyle regardless of the distance traveled. The second test was calculating the distance traveled during 25m freestyle regardless of motor performance. The researcher concluded that wrong past experiences have a negative effect on learning correct movements of freestyle in swimming. In addithion to that, students with no swimming experiences are better in learning the correct movements of freestyle. Finally the researcher recommended the necessity of concentrating upon teaching correct swimming movements for all students during swimming lessons whether they know how to swim or don’t know. He also recommended correcting the mistakes of performance and increasing repetitions for students who have wrong past experience through swimming lessons.